Ihdad Bagi Perempuan Karir Studi Komparatif KHI dan Fiqih Imam Syafi’i - Khairul Imam Karami; Lalu Muhammad Nurul Wathoni (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The article discusses the comparison of Ihdad provisionbetween KHI and Imam Syafi’i. KHI states that Ihdad must be done during ‘iddah for wives left by their husband due to death as a symbol of grief and avoidin slender. These wives, according to Imam Syafi’i, must do Ihdad in case they are adults, children, kafir dzimmis, or slaves. The distinctive is also found in the law consequence that should be accepted during Ihdad. In KHI there is no law that sets things forbidden during Ihdah in details as Imam Syafi’i’s fiqh provision.